DOI: 10.3384/diss-diva-134595
|View full text |Cite
|
Sign up to set email alerts
|

TRIAGE : Management of the trauma patient

Abstract: Triage, derived from the French word for sorting, aims to assess and prioritize injured patients, regardless of whether the injuries are sustained from everyday road traffic accident with few injured or a mass casualty incident. Triage seeks to provide the greatest benefit to the largest number of casualties in order to minimize morbidity and mortality. Triage in a pre-hospital setting entails management and sorting of patients according to an assessment of medical need, prioritization, and evacuation. In-hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 102 publications
(149 reference statements)
1
1
0
1
Order By: Relevance
“…The participants in the present study also described that no common method of triage was used. This finding is in line with others who described that a lack of a common method of triage could create confusion among emergency service personnel and delay essential treatment (Lampi, 2017; Advanced Life Support Group, 2012). A potential countermeasure is described by Nilsson et al.…”
Section: Discussionsupporting
confidence: 89%
“…The participants in the present study also described that no common method of triage was used. This finding is in line with others who described that a lack of a common method of triage could create confusion among emergency service personnel and delay essential treatment (Lampi, 2017; Advanced Life Support Group, 2012). A potential countermeasure is described by Nilsson et al.…”
Section: Discussionsupporting
confidence: 89%
“…A study in Moi Teaching and Referral Hospital in Kenya found that triage skills were lacking even among the physicians and that experienced pre-hospital personnel are more skilled than specialists in hospital settings [17]. This is because of the working environment in the pre-hospital set up which is not as organized as in the health facility set up.…”
Section: Prioritization Of Casualtiesmentioning
confidence: 99%
“…Pemberian pendidikan kesehatan dapat meningkatkan pengetahuan atau wawasan tentang bencana dan tindakan saat pada fase pra bencana, saat bencana dan pasca bencana gempa bumi khususnya pasa fase pra bencana pencegahan dan mitigasi untuk mengurangi dampak dari bencana (Febriawati et al, 2020). Pemberian pelatihan berupa pemberdayaan yang bisa di lakukan untuk mengatasi dampak yang akan ditimbulkan apabila gempa susulan terjadi lagi maka tim pengabdian mengadakan penyuluhan dan pelatihan yaitu Pelatihan GEPID (Triage dan Rapid Treatment) (Lampi, 2017). GEPID (Triage dan Rapid Treatment) adalah tindakan penyelamatan pasien yang tengah mengalami gangguan medikal ataupun trauma.…”
unclassified